2019
DOI: 10.7759/cureus.4701
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a High-risk Thoracolumbar Compression Fracture Using Bilateral Expandable Titanium SpineJack Implants

Abstract: In this case, an 80-year-old active patient developed an acute osteoporotic fracture after a fall at L1 above a previous interlaminar implant at L4-5 for stenosis with neurogenic claudication. Radiologic studies found both intra-discal and intra-vertebral vacuum clefts that are highly correlated with instability and progressive kyphosis. Long-term experience with kyphoplasty has shown that acute and subacute fractures can often be re-expanded; however, over three months to one year, the correction is frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The improvement in VAS scores was more marked in the patients undergoing interventional cement injection with the greatest treatment efficacy seen with insertion of expandable implants. This finding was previously reported on a study of use of the SJ R implants in treating VP fractures [8,9].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The improvement in VAS scores was more marked in the patients undergoing interventional cement injection with the greatest treatment efficacy seen with insertion of expandable implants. This finding was previously reported on a study of use of the SJ R implants in treating VP fractures [8,9].…”
Section: Discussionsupporting
confidence: 85%
“…All of these can be performed under local anesthesia, often in an outpatient setting [5,6]. Despite large experience with percutaneous treatment of fractures, VP fractures have often been listed as a contraindication for vertebral augmentation assuming it was technically difficult or impossible to cannulate the severe compression, and that percutaneous augmentation procedures would not provide sufficient expansion, height restoration, and reduction of kyphosis compared to open surgery [1,2,[7][8][9]. This is a retrospective review of 100 patients found to have a total of 110 severe osteoporotic vertebral fractures with greater than 50% vertebral collapse.…”
Section: Introductionmentioning
confidence: 99%
“…In cases with clefts, movement of the fracture within the vertebrae with flexion and extension films can show the cleft enlarging, and this motion is reported to correlate with either a balloon or internal expanding device being especially effective in restoring vertebral height [ 13 ]. It is clear in the literature that with the existence of a vertebral cleft regardless of the approach used (vertebroplasty, kyphoplasty, or implants), it is critical at the time of the procedure to ensure cement fill within the cleft, or there is a much higher incidence of progressive collapse and eventual failure of the procedure can occur [ 6 , 12 , 13 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Axial views allow assessment of optimal angle of convergence while estimating the angle for safe transpedicular approach. Ideal placement of the implants is positioning posteriorly just from the vertebral base of the pedicle and passing anteriorly just lateral of the midline so that both implants together form a "V" with the maximum support along a line from the pedicle proceeding bilaterally in the anterior part of the vertebral body [ 7 , 8 , 16 ]. This provides for best expansion and mechanical support especially in the maximum area of collapse in the mid and anterior vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, a 4.2-mm implant was used, which expanded to 12.5 mm height x 20 mm length, and the addition of bone cement provided significantly larger volumetric support centered under the collapsed endplate bilaterally. Clinical experiences with the implant, especially in the treatment of primary thoracolumbar osteoporotic fractures at this level, supports this approach in failed kyphoplasty or recurrent fractures too [15,20].…”
Section: Discussionmentioning
confidence: 85%